Inhibition of CISD2 enhances sensitivity to doxorubicin in diffuse large B-cell lymphoma by regulating ferroptosis and ferritinophagy - Zhang, Chaofeng; Zhan, Siting; He, Yanjun; Pan, Zhiqun; You, Zhongyi; Zhu, Xiongpeng; Lin, Qi (Frontiers in Pharmacology, 2024)
Background CDGSH iron-sulfur domain 2 (CISD2), an iron-sulfur protein with a [2Fe-2S] cluster, plays a pivotal role in the progression of various cancers, including Diffuse Large B-cell Lymphoma (DLBCL). However, the mechanisms by which CISD2 regulates the occurrence and development of DLBCL remain to be fully elucidated. Methods The potential role of CISD2 as a predictive marker in DLBCL patients treated with the R-CHOP regimen was investigated through bioinformatics analysis and clinical cohort studies. DLBCL cell lines (SUDHL-4 and HBL-1) were employed in this research. Adenoviral (AV) plasmids were used to either silence or overexpress CISD2 in these DLBCL cell lines. Additionally, the induction of ferroptosis in DLBCL cell lines was assessed. Various parameters, including cell proliferation, intracellular free iron levels, lipid peroxides, reactive oxygen species (ROS), and mitochondrial membrane potential (MMP), were measured. Furthermore, the expression of proteins associated with ferroptosis and ferritinophagy was analyzed. Drug-resistant DLBCL cell lines were developed by gradually increasing doxorubicin (DOX) concentration over six months. The biological role of CISD2 in these drug-resistant DLBCL cell lines was subsequently assessed. Results Elevated CISD2 levels were found to be associated with decreased sensitivity of DLBCL patients to the R-CHOP regimen, as indicated by bioinformatics and clinical cohort analysis. Silencing CISD2 significantly reduced cell proliferation, increased iron accumulation, depleted glutathione (GSH), and elevated malondialdehyde (MDA) levels, alongside the accumulation of ROS and increased MMP. Additionally, BECN1 and NCOA4 expressions were upregulated, while p62, FTH1, and GPX4 expressions were downregulated. Conversely, overexpression of CISD2 reversed these effects. Treatment of DLBCL cell lines with Erastin led to decreased CISD2 levels. Notably, in drug-resistant DLBCL cell lines, CISD2 knockdown promoted ferroptosis and ferritinophagy, restoring sensitivity to DOX and enhancing the efficacy of Erastin treatment. Conclusion Our findings suggest that CISD2 may play a role in the drug resistance observed in DLBCL patients. Inhibition of CISD2 could enhance ferroptosis and ferritinophagy, potentially improving the sensitivity of DLBCL cells to DOX treatment.